ANALISIS BUSINESS PERFORMANCE BERDASARKAN KARAKTERISTIK RESPONDEN: JENIS KELAMIN, TINGKAT PENDIDIKAN DAN USIA STUDI DI DESA WISATA DAERAH ISTIMEWA YOGYAKARTA - Ahsan Sumantika; Adhi Prakosa (Optimum: Jurnal Ekonomi dan Pembangunan, 2019)
The development of tourism in Indonesia several years has increased. Oneof the tourist destinations that can be visited is the tourism village. Tourism Village is a village that has a product/service with a special characteristic. To increase tourism potential, marketing strategies are needed to attract tourists, while business performance demonstrates the business performance of an organization. The purpose of this research is to highlight demographic problems that test if there is a diff erence in business performance based on demographic characteristics that are tested that is gender, level of education and age of respondents. The subject in this study is the owners of SMEs in the tourist villages in the special region of Yogyakarta with a total sample of 116 respondents. Data is retrieved through questionnaire. The method of analysis used is a diff erent test one way ANOVA. Test results show that there is nosignifi cant diff erence in business performance based on gender or level of education. However, other results show signifi cant diff erences in business performance based on respondents age.